DAMPAK POLITIK IDENTITAS PADA PEMILIHAN UMUM 2024 MENDATANG - Andre Pebrian (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
Identity politics will continue to be present in Indonesia’s political narrative towards the upcoming 2024 presidential election. Because the mental condition and character of the Indonesian people have not been separated from the sentiments of primordialism and sectarianism which are still firmly rooted in the culture of Indonesian society even though they have lived in the open democratization era and the modern digitalization era. The term identity politics has long been constructed as a political narrative by certain political elite groups in Indonesia as an instrument discourse to describe feelings of hatred and fear of losing to their political opponents in order to reduce the image and corner certain figures who are usually considered strong and have the potential to win, can defeat other opponents. so it needs to be cornered with non-nationalist and intolerant narratives. Identity politics is basically a political situation and method that unites groups due to a sense of injustice and dissatisfaction based on the equality of group backgrounds, for example ethnicity, race, religion and gender. Identity is not only a sociological matter but can also enter the realm of politics. Identity politics can have both good and bad effects in this diverse republic. Keywords: Impact, Identity Politics, General Elections